Ocular Surface Biomarkers. Issue 5 (May 2021) - Simsek, Cem; Dogru, Murat
Abstract : Abstract: Sjögren syndrome (SS) is a chronic inflammatory autoimmune disease of the lacrimal and salivary glands. Salivary gland biopsy is still one of the most valuable and acceptable diagnostic tests for SS, which however, is an invasive test. Therefore, noninvasive diagnostic biomarkers with high specificity and sensitivity are required for the diagnosis and assessment of SS. Because ophthalmological testing constitutes to an important part for the diagnosis of SS. Tears harbor biomarkers with a high potential to be used for differential diagnosis and assessment of treatment in many systemic disorders, including SS. This review aims to summarize recent advances in the identification of tear biomarkers of SS, trying to identify reliable, sensitive, and specific biomarkers that can be used to guide treatment decisions.